Traumatic injuries of young primary and permanent teeth: multimedia for Stomatology students - Jorge Lázaro Cruz Pérez; Leonardo Antonio Bueno Almaguer; Yadiana Estrada Mirabal; Melissa Ferrá Feo; Damaris Jiménez Martín; Odalys Martín Reyes (Universidad de Ciencias Médicas de Granma, 2021)
Oral dental trauma is a frequent accident that affects the morbidity of the primary and permanent dentition, therefore the dentist should be prepared to carry out a careful study of the case and provide adequate treatment to preserve the dentition and avoid biopsychosocial disorders in the patients and their families. Aim: to develop a multimedia of "Traumatic injuries in young primary and permanent teeth" for Stomatology students. Method: a technological innovation study was carried out during the 2019-2020 school year, at the Camagüey University of Medical Sciences. Different computer programs were used for the development of the multimedia, as well as theoretical and empirical methods. The multimedia proposal was evaluated by experts using the Delphi method. The universe was made up of 30 experts, from which a sample of 20 experts was selected who met the inclusion, exclusion and exit criteria. Results: 75 % of the experts were female, 50 % of them had between 6 and 10 years of teaching experience and 75 % had a Master's degree in Sciences. More than 95% of the teachers judged all the dimensions as very adequate. Only the contribution to the preparation of the subject was classified as fairly adequate (5 %) and the relevance of the images to the purpose of the software was considered adequate (5 %). Conclusions: an educational multimedia was developed as a useful tool for the teaching-learning process related to dental trauma of young primary and permanent teeth, intended for students and professionals of stomatology, which was validated by experts as very adequate for its use in the teaching field.